Pengaruh Financial Literacy, Representativeness Bias, Dan Bias Optimisme Terhadap Pengambilan Keputusan Investasi - Silvia Putri; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to analyze 1) whether there is an influence of financial literacy on investment decision maknig. 2) Obtain empirical evidence whether there is an Representativeness bias making on investment decisions. 3) Does Bias optimisme affect investment decision making. In this study using Causality Design. Population and sampek are 104 respondents registered in the Indonesia Stock Exchange Investment Gallery (GIBEI) Faculty of Economics, State University of Padang. The method of analysis is multiple linear regression. The results of the study found 1) Financial literacy influences investment decisions on investment decision making.2) Optimum bias affects investment decisions on investment decision making. 3) Representativness influences investment decisions on investment decision making. 4) Together financial literacy variables, the optimum bias and representativness together influence the investment decision on investment decision making